The Perfect Hope : Inn Boonsboro Trilogy #3 - Roberts, Nora; Andrews, MacLeod (Grand Haven, Mich. : Brilliance Audio, 2012)
Innkeeper Hope Beaumont's past makes an unwelcome appearance as she adjusts to life in small-town Boonsboro and her attraction to tough and surly Ryder Montgomery.
Unabridged.
Compact discs.
Read by MacLeod Andrews.
Keywords: Brothers -- Fiction; Bed and breakfast accommodations -- Fiction; Man-woman relationships -- Fiction; Boonsboro (Md.) -- Fiction; Audiobooks; Romance fiction